An Update on the Role of Serotonin and its Interplay with Dopamine for Reward - Fischer, Adrian G.; Ullsperger, Markus (Frontiers in Human Neuroscience, 2017)
The specific role of serotonin and its interplay with dopamine in adaptive, reward guided behavior as well as drug dependence, still remains elusive. Recently, novel methods allowed cell type specific anatomical, functional, and interventional analyses of serotonergic and dopaminergic circuits, promising significant advancement in understanding their functional roles. Furthermore, it is increasingly recognized that co-release of neurotransmitters is functionally relevant, understanding of which is required in order to interpret results of pharmacological studies and their relationship to neural recordings. Here, we review recent animal studies employing such techniques with the aim to connect their results to effects observed in human pharmacological studies and subjective effects of drugs. It appears that the additive effect of serotonin and dopamine conveys significant reward related information and is subjectively highly euphorizing. Neither dopamine nor serotonin alone have such an effect. This coincides with optogenetically targeted recording in mice, where the dopaminergic system codes reward prediction errors, and the serotonergic system mainly unsigned prediction errors. Overall, this pattern of results indicates that joint activity between both systems carries essential reward information and invites parallel investigation of both neurotransmitter systems.